Combating weight-stigmatization in online spaces: the impacts of body neutral, body positive, and weight-stigmatizing TikTok content on body image and mood - Kilby, Raeanna; Mickelson, Kristin D. (Frontiers in Psychiatry, 2025)
Social media movements centered on body positivity and body neutrality both encourage healthy attitudes toward the physical body; however, these movements are conceptually distinct and may have unique influences on body image. This study examined how brief exposure to different types of body acceptance and weight-stigmatizing content affects body image and mood. Participants consisted of women and gender-diverse individuals (N = 326) who completed an online survey and were randomly assigned to view one of four TikTok video compilations: body neutrality, body positivity, weight-stigmatizing, or travel (control) content. Exposure to body positivity and body neutrality content was associated with improvements in functional appreciation, self-objectification, body dissatisfaction, and negative affect. Moreover, although participants across body-focused conditions reported thinking about their appearance to a similar extent, those in the body-positive and body-neutral groups reported more frequent positive appearance-related thoughts than those in the weight-stigmatizing or control conditions. Importantly, differences emerged between the two body acceptance conditions, such that body neutrality was uniquely effective in reducing self-objectification relative to weight-stigmatizing content, while body positivity significantly enhanced positive affect. Moderation analyses revealed marginal interactions, suggesting that the effect of content on body dissatisfaction varied by gender identity, while positive affect varied by perceived body silhouette. Overall, these findings indicate that body-positive and body-neutral content on TikTok may serve as beneficial alternatives to weight-stigmatizing media, though each approach may yield distinct benefits especially in consideration of individual identity characteristics.